A grain size and n-alkanes record of Holocene environmental evolution from a groundwater recharge lake in Badain Jaran Desert, Northwestern China. (June 2019) - Kai, Ning; Naiang, Wang; Xiaonan, Lv; Zhuolun, Li; Jiaqi1, Sun; Ran, An; Lvlv, Zhang
Vertical water transport plays an important role in the development and maintenance of lakes in arid zones. However, previous study of this phenomenon has focused mainly on the effects of regional precipitation, rather than effects of groundwater recharge, on arid-zone environmental change. We selected a sedimentary profile from a seasonal lake basin located in the hinterland of the Badain Jaran Desert, northwestern China, to assess the Holocene environmental evolution of this region and its response to climate change. Our results show that peat deposition from 11 to 10 ka indicates humidification after Younger Dryas (YD) event; the lake sediment and lower EM2 and lower principal component analysis (PCA)-1 scores indicate relative more humid environment from 10 to 7.8 ka; the lake sediment and higher EM2 and higher PCA-1 scores indicate most humid environment from 7.8 to 5.8 ka; the transition from lacustrine facies to limnetic facies and increasing salinity indicate drying trend from 5.8 to 2.5 ka; the aeolian sand sediment and lowest EM2 and lowest PCA-1 scores indicate driest environment from 2.5 to 0.8 ka; and lacustrine facies and finest grain size indicate relative humid environment during the 'Little Ice Age' period. The environment was relative humid in early Holocene, most Humid in mid-Holocene, and dry in mid-late Holocene. The moisture pattern in the hinterland of the Badain Jaran Desert was synchronous with that in the northeastern of Tibetan Plateau, which implies that the groundwater recharge lake was dominated by the intensity of groundwater recharge from monsoon margin area, especially the northeastern of Tibetan Plateau. As a record from groundwater recharge lake without runoff, our study provides the groundwater output quantity record from northeastern of Tibetan Plateau and would benefit the environment change research and regional water resources allocation around the Tibetan Plateau.